2012
DOI: 10.1200/jco.2012.30.18_suppl.3
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine plus rituximab (B-R) versus CHOP plus rituximab (CHOP-R) as first-line treatment in patients with indolent and mantle cell lymphomas (MCL): Updated results from the StiL NHL1 study.

Abstract: 3 Background: This multicenter, randomized, phase III study compared B-R and CHOP-R as first-line treatment in indolent lymphoma and MCL and was presented at ASH 2009 including a comprehensive safety analysis. Here we present an updated analysis with a cut-off date for 31 Oct 2011. Methods: 549 patients (pts) with indolent or MCL were randomized to receive B-R or CHOP-R for a max of 6 cycles. The primary endpoint was PFS. Results: 514 pts randomized pts were evaluable (261 B-R; 253 CHOP-R). Patient characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 0 publications
5
47
0
1
Order By: Relevance
“…By the end of the combined regimen, 88% of the patients had achieved CR. More importantly, with a median By comparison with the other competing chemotherapies, our study confirmed an important percentage of CRs higher than those obtained with CHOP-R, CVP-R, and BR regimens [4][5][6]9,10] and an impressive DFS (also in terms of a median follow-up period) higher than those reported for the other chemoimmunotherapies.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…By the end of the combined regimen, 88% of the patients had achieved CR. More importantly, with a median By comparison with the other competing chemotherapies, our study confirmed an important percentage of CRs higher than those obtained with CHOP-R, CVP-R, and BR regimens [4][5][6]9,10] and an impressive DFS (also in terms of a median follow-up period) higher than those reported for the other chemoimmunotherapies.…”
Section: Discussionsupporting
confidence: 62%
“…This scenario was also the same extrapolated from the final report of ILL-FOLL05 trial [12]. An another competitor is the new entry BR regimen that appears to induce a longer PFS and to be better tolerated than CHOP-R [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Updated results after 7 years of follow-up from the stil1 study demonstrated that br has pfs and time-to-next-treatment benefit over r-chop. Although the os for the patients overall was not significantly different, treatment with br was associated with a trend toward survival benefit in the group of patients with indolent lymphomas 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Updated results presented at the American Society of Hematology 2014 annual meeting showed that median time to next treatment in the br group still had not been reached after a median follow-up of 87 months 5 . In the stil-1 trial, maintenance rituximab was not given, but maintenance is routinely used in Canada; therefore, time to next treatment could in reality be even longer with br.…”
Section: Introductionmentioning
confidence: 99%